A study on the communication patterns of overseas Filipino workers and their families in Cabanbanan, Manaoag, Pangasinan - Arinzana, Jade Valdez; Mohamad, Caressa Yu (2006)
This is case study on the communication patterns of families whose parents are working abroad as Overseas Filipino Worker (OFW) in Barangay Cabanbanan, Manaoag, Pangasinan. It determined the family communication patterns between and among the children and their parents working abroad. This study also provided a descriptive analysis on their means of communication, how the parents and their children maintained and established a good and harmonious relationship with each other, and the level of openness and self-disclosure during communication situations. Based on the result, the maintenance of the interactional relationship between OFW parent and children left behind is sustained through constant telephone calls and instant text messaging. Also, communication patterns among OFW parents and their familes became more conducive through the technological advances like emails and telephone calls. Likewise, children with OFW parents tend to grow up responsibly and maintained good and open relationships with their parents despite their distance.
Thesis (Bachelor of Arts in Communication)--University of the Philippines Baguio, 2006.
Includes bibliographical references.
Keywords: Interpersonal communication -- Philippines -- Manaoag (Pangasinan); Parent and child -- Philippines -- Manaoag (Pangasinan); Communication in families